A guided tour of the world of rational expectations models and optimal policies - Philippe Jeanfils (National Bank of Belgium, 2001)
This working paper after quickly reviewing the different types of existing macro models presents some basic tools that have proved useful for analysing monetary policy in recent years. Through the use of a simple quantitative forward-looking model of output, inflation and interest rate determination, the paper tries to familiarise the reader with some of the techniques used in research on optimal policy, including rational expectations theory, timeconsistency analysis, the Lucas critique and computer simulation techniques. The explanation proceeds gradually. First, a single linear difference equation is used to explain how solutions to models with forward-looking expectations can be obtained. Then it deals with methods used to solve more general models for optimal policies. Finally, the potential usefulness of these techniques is explained through a series of applications to monetary policy.
Keywords: 330; Geldpolitik; Makroökonomik; Rationale Erwartung; Zeitkonsistenz; Neue klassische Makroökonomik; Simulation; Theorie